Local community’s perception on the existing home stay program in Terai and Hilly districts of Nepal - Saud, Tul Bahadur; Menariya , S. L. (Nepal Journal of Multidisciplinary Research, 2021)
Homestay tourism program is a new part of tourism sector which involved local community in tourism development within their own and surrounding area. It is also lately emerging tourism concept in the world. Nepal is known as an important tourist’s destination and can be a model homestay country with its abundant natural resources, multi culture, multi religion, multi ethnic, tradition life style, archeological heritage, innocent society and community. Due to all these above factors homestay tourism program became the dream for the lover of nature and experts of tourism in Nepal. Homestay program can be easily established, Promoted and developed by minimum investment and based on many aspects such as good service, safety, security, souvenir, family and attractions. It is a major tourism industry for the development of rural economy by generating huge number of employment and social benefits. The major objective of the study is the perception of community towards homestay tourism program. Descriptive and exploratory research design, cross-sectional study design and deductive approach with mixed method have been used in this study. Both primary and secondary data are used simultaneously. Primary data are collected from 348 respondents with three categories of nine study Districts. Similarly, secondary data are collected from various publications of central, state, local Governments, different articles in international journals, books, credible magazines, newspaper, reports prepared by research scholars, experts and universities and different websites etc. Finally, majority of community people have a positive perception towards on existing homestay program in Nepal.